(untitled) (Bangladesh Journal of Botany, 2021)
Effects of foliar applied macro (NPK) and micro nutrients (Fe, Mn, Zn, Cu and B) at different time on yield, quality and benefit: cost ratio of rainy and winter season guava were evaluated in north western Haryana, India. The two season’s data depicted that physico- chemical characters with respect to fruit set, fruit retention, fruit size, average fruit weight and yield were significantly increased with foliar application of macro and micro nutrients at vegetative, flowering and fruiting stage (T7). The shoot C: N ratio was also found highest with T7 foliar treatment which was followed by T5 in both the seasons. The T7 foliar spray resulted in maximum benefit: cost ratio in both the seasons. Proper fertilization strategies can help fruit growers to get good yield and quality fruits. Bangladesh J. Bot. 50(4): 1159-1164, 2021 (December)